Potential Locations for Noninvasive Brain Stimulation in Treating Autism Spectrum Disorders—A Functional Connectivity Study - Huang, Yiting; Zhang, Binlong; Cao, Jin; Yu, Siyi; Wilson, Georgia; Park, Joel; Kong, Jian (Frontiers in Psychiatry, 2020)
Objectives: Non-invasive brain stimulation (NIBS) is an emerging tool for treating autism spectrum disorder (ASD). Exploring new stimulation targets may improve the efficacy of NIBS for ASD. Materials and Methods: We first conducted a meta-analysis on 170 functional magnetic resonance imaging studies to identify ASD-associated brain regions. We then performed resting-state functional connectivity analysis in 70 individuals with ASD to investigate brain surface regions correlated with these ASD-associated regions to identify potential NIBS targets for ASD. Results: We found that the medial prefrontal cortex, angular gyrus, dorsal lateral prefrontal cortex, inferior frontal gyrus, superior parietal lobe, postcentral gyrus, precentral gyrus, middle temporal gyrus, superior temporal sulcus, lateral occipital cortex, and supplementary motor area are potential locations for NIBS in ASD. Conclusion: Our findings may shed light on the development of new NIBS targets for ASD.